Differences in students' academic achievement based on the level of parental involvement at SDI Ash-Sholihah - Mifta Mairani Noor; Munawir Pasaribu; Robie Fanreza (Lembaga Riset Mutiara Akbar, 2026)
This study examines differences in students’ academic achievement based on levels of parental involvement at SDI Ash-Sholihah Gedung Johor. A quantitative comparative design was employed with a sample of 84 students selected from a population of 540 using the Slovin formula (10% error rate). Data were collected through validated and reliable questionnaires measuring parental involvement and academic achievement, and analyzed using descriptive statistics, one-way ANOVA, and Tukey HSD tests. The findings revealed that mean academic achievement differed significantly across parental involvement levels: low (61.46), medium (66.86), and high (74.39). The ANOVA test indicated a statistically significant difference (F = 44.795; p less than 0.05), and post hoc analysis confirmed that students with high parental involvement achieved significantly higher scores than those in medium and low groups. These results demonstrate that parental involvement is a crucial external factor influencing academic success. The study highlights the importance of strengthening school–family collaboration to enhance learning outcomes, particularly in Islamic elementary school contexts. The findings contribute empirical evidence supporting educational policies and practices that actively engage parents as partners in students’ academic development.